Aspectos epidemiológicos relacionados à ocorrência de ácaros hematófagos em granjas comerciais de postura no Estado de Minas Gerais e avaliação de armadilhas para captura de Dermanyssus gallinae (ACARI: DERMANYSSIDAE) (DE GEER, 1778) - Lucas Maciel Cunha (2013)
Studies were conducted for evaluating some aspects of the occurrence of hematophagous mites in commercial chicken layer houses in Minas Gerais State, Brazil. Methods for the capture of poultry red mites Dermanyssus gallinae were investigated by comparing corrugated paper traps (CPT) and taquaril bamboo (Phyllostachys sp.) straw as hiding place traps, in which developmental instars may be found. No difference was found in egg oviposition between traps (Chi Square test, p > 0.05). However, significant differences were found regarding mobile instars between traps (Wilcoxonss test, p 0.01), with CPT capturing more mite mobile instars than bamboo straw traps. CPT traps were used in subsequent epidemiologic study of D. gallinae. Observational, analytical and sectional surveys were also conducted in order to verify the epidemiological risk factors for the occurrence of infestation of different species of Acari in poultry flocks of commercial production systems in the State of Minas Gerais, Brazil. CPT collection, direct chicken integument inspection and the application of a questionnaire were employed in two studies in 431 commercial layer houses. Twenty-three out of 43 poultry farms (53.48%) had Ornithonyssus sylviarum, and 16 (37.21%) had Ornithonyssus bursa. D.gallinae was found in two farms (4.65%). No mites were observed in flocks subjected to molt or poultry raised on floor. Mite risk factors were evaluated utilizing multiple logistic regression models. In the first study, wooden fence was evidenced as the major risk factor for D. gallinae. Poultry red mite was not detected in farms using acaricides in feed. A third conjunct of studies evidenced that the major risk factors of O. bursa were the presence of synanthropic rodents, hensproximity to subsistence chickens, chicken breed and geographical area. The risk factors for the presence of O. sylviarum were Norway Rat (Rattus norvegicus) around poultry houses, presence of Saffron Finch (Sicalis flaveola), presence of Cattle Egret (Bubulcus ibis), chicken breed and geographical area